Microbial diversity and cellulase activity of forest soils and litters - Malcheva, Boyka; Grigorova-Pesheva, Bilyana; Hristov, Biser (Edelweiss Applied Science and Technology, 2024)
The quantity, composition and cellulase activity of forest soils and litters with deciduous and coniferous tree vegetation on the territory of Natural Park "Vitosha" were investigated. Biogenicity, the rate of decomposition of organic matter and specifically of cellulose decomposition were higher in Fagus sylvatica litters than in Pinus sylvestris. In most soil profiles, the total microflora has higher values in the mixed fermentative and humic layer of the litter compared to the fresh litter. The quantity of microorganisms and cellulase activity decrease in the depth of the soil profiles. In general, non-spore-forming bacteria, followed by mold fungi and bacilli, occupy a major share in the composition of the total microflora in litters and soils, and actinomycetes are less represented. The cellulase activity depends to the highest degree on the non-sporulating bacteria, and the values of the mineralization coefficient on the bacteria assimilating mineral nitrogen. The humidity of the litters and soils has a stronger influence on the development, composition, mineralization and cellulase activity of microorganisms, compared to the altitude.